Allelopathic inhibition of the extracts of Landoltia punctata on Microcystis aeruginosa. (31st December 2022) - Dan, Li; Peng, Li; Zhiqiang, Yan; Na, Li; Lunguang, Yao; Lingling, Cao
ABSTRACT: To study the allelopathic effect of the extracts of Landoltia punctata, the changes of cell density of Microcystis aeruginosa were measured. The anti-algae allelopathic effect of different organic solvent extracts of L. punctata was evaluated, and the physiological, biochemical indexes were determined to discuss the mechanism of algal inhibition. The results showed that the petroleum ether, dichloromethane and ethyl acetate extracts showed various inhibitory effects on M. aeruginosa . Among them, ethyl acetate extract was the most strongly allelopathic part with the semi-effect concentration(EC50 ) of 59.6 mg L −1, the central polarity part of inhibitory activity. The contents of chlorophyll a(Chl a) and phycobiliproteins(PBPs) of M. aeruginosa were decreased under the concentration of 200 mg L −1 ethyl acetate extract, which indicated that the photosynthesis of M. aeruginosa was inhibited. The consent of microcystins was lower compared to control under 200 mg L −1 . The contents of superoxide dismutase(SOD), malondialdehyde(MDA) and hydrogen peroxide(H2 O2 ) of cell pellets were firstly increased and then decreased, which suggested that the algal cells were seriously damaged by oxidation. The results indicated that the extracts of L. punctata had inhibitory effect on M. aeruginosa, and the ethyl acetate extract was the central part of the inhibitory substances, which affected photosynthesis and caused peroxidation damage to inhibit cell proliferation. These findings will be helpful for exploration and application of allelopathic effects of L. punctata in harmful algae control.